Inventory Of Open Space And Vegetation In Unsrat Campus Based On Ui Greenmetric - Nurmawan, Wawan; Ogie, Tommy Bartholomeus; Polakitan, Derek J. (Jurnal Agroekoteknologi Terapan, 2025)
Universities play a pivotal role in advancing sustainability through effective management of open spaces and vegetation. This study assesses the condition of green open space and vegetation on the Sam Ratulangi University campus using the UI GreenMetric framework, focusing on the Setting and Infrastructure category. A comprehensive field inventory was conducted across 16 campus locations, recording 74 tree species and a total of 1,972 individual trees, with Swietenia macrophylla (large-leaf mahogany) as the dominant species. The university achieved a total score of 500 out of 1,500 possible points in this category. The highest score was observed in SI 2 (proportion of forest vegetation), which received the maximum 200 points, demonstrating effective maintenance of forested areas. However, SI 5 (ratio of green open space per capita) scored zero, indicating inadequate accessible green space for the campus community. These findings highlight both strengths and challenges in current sustainability practices. Addressing these gaps requires integrated planning to improve green space distribution and enhance campus livability. The study underscores the importance of expanding assessment to other university locations to gain a holistic view of institutional sustainability. Such efforts are essential for informed decision-making, promoting biodiversity conservation, improving environmental quality, and supporting the university’s commitment to achieving higher UI GreenMetric rankings. Keywords: UI Green Metric, Infrastructure, Sam Ratulangi University Campus, Vegetation